Stakeholders' perception of test security as management tool for curbing malpractices in the Nigerian public examining system (2009)
The paper examined how test security measures can be integrated in the public examing system to curb the menace of examination mal practice that has become a regular feature of the Nigeria public examining system. In a survey type of research, questionniare was administered on some stakeholders made up of officials and ad hoc staff of examining bodies, parents and examinees. The data was analysed using percentages and chi-square statistics. Findings include: stakeholders who are causes of the various forms of malpractice have to be sensitized on the need to fight the menace, test security intelligent group should be formed to nip the menace and tri-dimensional security approach (proactive which considers security issues as part of the whole system from commencement of test development, concurrent security which is made part of the adminstration of the examining instrument and retrospective measure to evaluate the entire process for improvement) be integrated in the Nigerian public examining system. This would call for increasing funding. Thus, it was recommended that all stakeholders should contribute more to the funding of public examining in the country and be concerned with the security of the testing system.